Contralateral Ocular Complication Following Dental Local Anaesthesia - Tengku Ahmad Noor, Tengku Natasha Eleena; Jacy, Wong Suet Yen (Faculty of Dental Medicine Universitas Airlangga, 2022)
Background: One of the most important aspects of dental surgery is the injection of local anesthetics, which control pain. Local anesthetics are administered close to certain nerves or fibers to block nerve transmission. Intraoral administration of local anesthetics, on the other hand, can affect other nerves, resulting in complications in the outside of the oral cavity. Ophthalmic problems are uncommon, accounting for about 0.04 to 0.1% of all complications Purpose: The purpose of this case is to discuss the unusual case of contralateral ocular complication following dental local anaesthesia. Case: We reported a 41 years old Malay male came to Kuching Armed Forces Dental Clinic for his appointment on surgical removal of impacted left lower wisdom tooth. After the minor oral surgery procedure under local anaesthesia has been done, the patient had a twitching right eye. Case Management: The patient's vital signs were checked to rule out the possibility of a stroke or anaphylactic shock. The patient was a sure to be calmed, laid down, and put cold compresses on both eyes with dim lighting. After 45 minutes of review, the patient was allowed to leave, followed by a two-week post-minor surgery check-up. Conclusion: Risk of complications from local anaesthesia can be reduced with the effective patient evaluation and anxiety management, correct injection technique, and sufficient knowledge of dental local anaesthesia.